A Modernized Approach to Managing the Risks in Cross-Border Capital Movements - Otker, Inci (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1999)
This paper outlines a 'modern' approach to managing risks in cross-border capital movements that is consistent with an environment of increased and liberalized capital flows. Key elements of this approach include: a consistent monetary and exchange rate policy mix to avoid incentives for volatile capital flows; prudential management of the specific risks in capital flows; supporting financial sector reforms; and appropriate sequencing of liberalization. The approach can reduce the potential size of the shocks associated with capital movements and increase the resilience of the financial system to such shocks when they occur; overtime, it is expected to reduce the need for recourse to capital controls.